Neural and Fuzzy Logic Control of Drives and Power Systems - Cirstea (M N); Dinu (A); Khor (J G); McCormick (M) (2002)
Neural ; Fuzzy Logic ;Drives ; Power Systems
22.5
Keywords: Neural ; Fuzzy Logic ;Drives ; Power Systems